PENGARUH KINERJA KEUANGAN DAN GAJI KARYAWAN TERHADAP PENGUMPULAN ZAKAT PADA BANK UMUM SYARIAH DI INDONESIA DENGAN DI MODERASI UMUR PERUSAHAAN - Cepi Juniar Prayoga; Dewi Susilowati (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2018)
This study aims to determine the effect of financial performance and employee salaries on the collection of zakat with the age of the company as a moderation variable with the object of research is Bank Syariah in Indonesia during 2013-2017. The method used in this research is quantitative method and the data used is secondary data. The sample used in this study is a sharia commercial bank that meets the specified criteria. The sampling technique using purposive sampling method. Data analysis used in this study is Multiple Regression Analysis and Moderate Regression Analysis (MRA). The results of this study indicate that financial performance and employee salaries have a significant effect on zakat collection. While the results of the Moderate Regression Analysis (MRA) show that the age of the company moderates the influence of financial performance on the collection of zakat and company age is not a moderating variable that can interact between employee salaries with the collection of sharia Islamic banks in Indonesia.